Are the sovereign CDS premia sound estimators of the stock market returns? Evidence from the Eurozone - Ana Navarrete Wic; Filippo Di Pietro; José Luis Martín Marín (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
In this paper, we explore the interconnection and existing relationships between the Sovereign Credit Default Swaps (henceforth, CDS) and the stock markets of the main European countries. Thus, the goal of this paper is to test if the CDS premia can predict the stock market returns of the most relevant economies within the Eurozone, so that, they serve as advanced indicators like mechanisms of price transmission. For this purpose, we apply the Granger Causality test to analyze ten main European stock markets from 2004 to 2016 by using daily data. Our hypothesis is proved to work for the largest economies with liquid CDS markets, whereas the transmission mechanism between CDS and stock prices is not so evident for the smallest ones.
Keywords: G12; G15; C22; C30; 330; CDS premia; stock market index return; Granger causality test; Eurozone; primas CDS; rendimiento de índices de mercado; test de causalidad de Granger; eurozona